AB0605 ridai.org/ssc: The Portuguese National Systemic Sclerosis Registry – Focus on Quality of Life and Data Conformity. (15th July 2016) - Matos-Costa, J.; Almeida, I.; Santos, L.; Delgado Alves, J.; Pinheiro, S.; Santos, M.; Dias, C.; Serradeiro, E.; Alves, G.; Vedes, J.; Brito, H.; Ferreira, P.; et al.
Abstract : Background: Registries have a major role in patient follow-up, prospectively collecting real life data, they help us to better understand rare diseases like scleroderma. These atabases allow standardization of daily clinical practice, introducing decision support tools and improving quality and health outcomes. They also allow drug and device surveillance; scientific societies, academia and regulatory authorities can analyze their selected core set of data. Methods: Our web-based registry - RIDAI (Informatic Registry of Autoimmune Diseases; www.ridai.org ), was created in 2003 by the Portuguese Society Internal Medicine to support all Autoimmunity Clinics in Portugal; currently collecting data from 40 centres, with 4825 patients with different diseases. It has been constantly developped to comprise all the updated tools to measure important domains in autoimmune diseases. Demographic and clinical data were collected and analysed in Microsoft Excel 2013. Results: Short presentation and demonstration of RIDAI, online since 2013. The scleroderma cohort has 326 patients, 227 limited and 99 diffuse subtypes, 43 (13.2%) males, mean age 56.4 (range 3–90), longest follow-up since 1993. Comorbidities are highly prevalent in our cohort: dyslipidemia in 46 patients, hypertension in 40, peripheral vascular disease in 22, osteoporosis in 20, heart failure in 13, diabetes in 10 and coronary heart disease in 3 patients. Most frequently used tools include Modified Rodnan Skin Score (mRSS), Visual Analogic Scale (VAS), Joint Count, EUSTAR Systemic Sclerosis Activity Scale (EUSTAR SSAS), the UCLA Scleroderma Clinical Trials Consortium Gastrointestinal Scale (SCTC GIT), Health Assessment Questionaire (HAQ) and Short Form-36 (SF-36). MRSS has a mean value of 9.1. Patient VAS has a mean 39.6; physician VAS mean 38.6. Painful Joint Count has a mean value of 3.0; tender Joint Count mean 1.6. The EUSTAR SSAS has a mean value of 1.27. SCTC GIT mean value is 0.52. HAQ mean value is 1.0; SF-36 mean is 103.9. Biological disease modifying drugs were prescribed off-label in 10 patients, for severe skin and joint disease. Conclusions: The RIDAI is the largest portuguese scleroderma registry. It's a versatile application and can be articulated with other platforms, with direct contribution to international multicentric studies. The presentation of the first 326 patients illustrates the complexity and heterogeneity of systemic sclerosis and of this cohort of patients. Treating to target and using standardized monitoring tools, Portuguese Internal Medicine physicians confirm good treatment performance, with a positive impact on indexes, specially mean mRSS and quality of life (HAQ, SF-36); enabling comparision with best practices. Disclosure of Interest: None declared